Gurdwara and its politics: Current debate on Sikh identity in Malaysia - Sarjit S. Gill,; Charanjit Kaur, (Universiti Kebangsaan Malaysia, 2008)
All Sikh functions, collective as well as individual, are generally performed in local Gurdwaras, which can play an essential role in developing the Sikh community. As Sikhism is a faith which recognises no division between religion and politics, in 1988 a central council of Gurdwaras called the Malaysian Gurdwaras Council was established to coordinate the functioning of these Gurdwaras. Based on our research, we found that, most of the Malaysian Gurdwaras face similar challenges. The ideal roles of the Granthi Sahib as a religious specialist are in question. The Granthi Sahib and Gurdwaras Management Committee (GMC) are in a dilemma about their roles. The reason for this conflict is explored in this paper. There are also conflicts between the GMC and Granthi Sahib due to committee members’ influence and their abuse of power in their relations with religious specialists. Therefore, the nature of role of the Malaysian Gurdwara Council in addressing these tensions which in turn affect the formation of Sikh identity is discussed